Confessions of an ugly stepsister - Maguire, Gregory 1954- (Regan Books, 2000)
On seeing her portrait, a servant girl modelling for an artist in 17th century Holland realizes she is ugly. But the portrait opens her eyes to the world of art, she becomes a painter and is transformed by her work so that when a prince charming appears she is no longer ugly.
Prologue : stories painted on porcelain -- 1. The obscure child -- Marketplace -- Stories told through windows -- Looking -- Meadow -- Sitting for Schoonmaker -- Girl with wildflowers -- Half a door -- Van den Meer's household -- 2. The imp-riddled house -- The small room of outside -- Small oils -- The masterpiece -- Rue, sage, thyme, and temper -- Reception -- Virginal -- Simples -- 3. The girl of ashes -- Flowers for the dead -- Plague and quarantine -- The nowhere windmill -- Invitations -- A fair light on a full table -- Wind and tide -- The girl of ashes -- Finery -- Spine and chamber -- Collapses -- 4. The gallery of God's mistakes -- Campaigns -- The gallery of God's mistakes -- Cinderella -- Van Stolk and van Antum -- The night before the ball -- The changeling -- Small magic -- Tulip and turnips -- 5. The ball -- The Medici ball -- Clarissa of Aragon -- Midnight -- A most unholy night -- The second slipper -- Epilogue : stories written in oils
Keywords: Beauty, Personal / Fiction; Fairy tales / Adaptations; Stepsisters / Fiction; Haarlem (Netherlands) / Fiction